Pengaruh Berbagai Jenis Kemasan Terhadap Umur Simpan dan Perubahan Fisiko-Kimia pada Buah Stroberi (Fragaria sp.) - HUTAJULU, ERNIA DESRIATI; MAHENDRA, MADE SUDIANA; ASTAWA, I NYOMAN GEDE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
The effect of using various packaging treatments on extend the shelf life of strawberry fruit and their physico-chemical changes Strawberry is one among horticultural commodities that has a significant potential being developed commercially in Bali. Strawberry fruit commonly has a relatively sweet taste and a strikingly bright red color. Strawberry fruit is easily damaged and has a short shelf life, so it is necessary to inhibit the damage, among others by the use of various packaging treatments. This study aims to extend the shelf life of strawberry fruit and the effect of using various packaging treatments on their physico-chemical changes. The experimental design used was completely randomized design with one packing type factor consisting of 3 treatment levels, ie without packaging, use of mica package, and use of styrofoam package. The results showed that strawberry fruits treated with mica and styrofoam pacgages had a longer shelf life than strawberry fruit stored without any packaging (control). The storage period of strawberries both treated with mica and styrofoam packeges were last up to the 4th day. The use of mica package showed the best results with the lowest shrinkage value, lowest softness, low respiration rate and high organoleptic value. Eventhough strawberry fruit packed with styrofoam package showed a high vitamin C content, but the strawberry fruit packed with mica package has a better visual appearance with good fruit quality and mostly accepted by the panelist.